STRUCTURAL AND TECHNOLOGICAL ASPECTS OF DECREASE IN WIRE ANNEALING AT A TWIST OF A HIGH-STRENGTH METAL CORD - V. Р. Fetisov (Литьë и металлургия, 2017)
Deformation by drawing with the raised share of the squeezing tension and application of additional deformation with small degrees in the line of a drawing camp allow to minimize a wire annealing of a cold-deformed wire during a twist of a highstrength metal cord.